2013
DOI: 10.1111/1574-6941.12137
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community and groundwater quality changes in an anaerobic aquifer during groundwater recharge with aerobic recycled water

Abstract: Managed aquifer recharge offers the opportunity to manage groundwater resources by storing water in aquifers when in surplus and thus increase the amount of groundwater available for abstraction during high demand. The Water Corporation of Western Australia (WA) is undertaking a Groundwater Replenishment Trial to evaluate the effects of recharging aerobic recycled water (secondary treated wastewater subjected to ultrafiltration, reverse osmosis, and ultraviolet disinfection) into the anaerobic Leederville aqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…These results suggest that P8 denitrification processes occur below the basin even when it is empty, indicating that 4 months is not enough time to revert back to natural conditions at this sampling point. This assumption is consistent with nitrate isotopic data presented in Grau-Martínez et al (2018) and is also in agreement with the study of Rodriguez-Escales et al (2016) in which biomass decay acted as an endogenous carbon source for respiration once the input carbon was reduced, maintaining denitrification rates.…”
Section: Matching Groundwater Model Ecological Disturbance Principlesupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggest that P8 denitrification processes occur below the basin even when it is empty, indicating that 4 months is not enough time to revert back to natural conditions at this sampling point. This assumption is consistent with nitrate isotopic data presented in Grau-Martínez et al (2018) and is also in agreement with the study of Rodriguez-Escales et al (2016) in which biomass decay acted as an endogenous carbon source for respiration once the input carbon was reduced, maintaining denitrification rates.…”
Section: Matching Groundwater Model Ecological Disturbance Principlesupporting
confidence: 91%
“…Biodegradation of EOCs strongly depends on redox conditions (Barbieri et al, 2011;Maeng et al, 2010). In this regard, it has been shown that MAR is a feasible technique capable of partially degrading some of these contaminants (Hellauer et al, 2017;Massmann et al, 2008), particularly when bioprocesses are enhanced (Grau-Martínez et al, 2018;Schaffer et al, 2015). Infiltration through the soil intrinsically leads to two main consequences in groundwater recharge:…”
Section: Barba Et Al: Microbial Communities In Marmentioning
confidence: 99%
“…As for microbial MAR field studies, most relevant research is limited to well injection systems (Ginige et al, 2013;Reed et al, 2008;Zhang et al, 2016) or riverbank filtration conditions (Huang et al, 2015). Onesios-Barry et al (2014) compared results from a column experiment and soil samples in a MAR site in the US, focusing on the micro-30 bial populations linked to pharmaceutical and personal care products removal, and concluded that microbial composition and structure of both systems were comparable.…”
mentioning
confidence: 99%
“…Aquifers harbour diverse microbial communities which can facilitate the natural attenuation of nutrients through microbial metabolic processes [63,64]. Microbial processes that facilitate nitrogen removal include aerobic ammonia oxidation, denitrification and anaerobic ammonia oxidation (Anammox) [65,66].…”
Section: Total Organic Carbon (Toc) and Other Nutrientsmentioning
confidence: 99%
“…As part of Perth's Groundwater Replenishment Scheme, Ginige et al [64] characterised the bacterial community within the anaerobic Leederville aquifer being recharged with aerobic reclaimed water using culture-independent molecular methods (clone library and QPCR of 16S rRNA genes) and flow cytometry. The study revealed that bacterial numbers increased and diversity decreased as a result of the aquifer recharge.…”
Section: Changes To Subsurface Microbial Ecologymentioning
confidence: 99%